Expans\~ao da fronteira agrícola no Brasil: Desafios e perspectivas - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The agricultural frontier is expanding in the direction of Brazilian Cerrado (about 22% of the country surface), mainly due to the intensive use of knowledge and technology. This study intends to do a regional economic analysis and calculate indicators that can measure the dynamics of productive spatial. Furthermore, it will be investigated the dimension of technology in the ability to save scarce resources. The expansion of grain and livestock farming is shown in the central of Brazil, including Matopiba region and the border in Amazon. It will be presented a diagnosis of this expansion, a land-saving effect analysis and the main logistical bottlenecks related to economic growth.
Keywords: Q16; R12; R42; 330; agricultural frontier; technology; infrastructure; logistics